Genomic profiling of multiple sequentially acquired tumor metastatic sites from an “exceptional responder” lung adenocarcinoma patient reveals extensive genomic heterogeneity and novel somatic variants driving treatment response - Biswas, Romi (Cold Spring Harb Mol Case Stud, 2016)
We used next-generation sequencing to identify somatic alterations in multiple metastatic sites from an “exceptional responder” lung adenocarcinoma patient during his 7-yr course of ERBB2-directed therapies. The degree of heterogeneity was unprecedented, with ∼1% similarity between somatic alterations of the lung and lymph nodes. One novel translocation, PLAG1-ACTA2, present in both sites, up-regulated ACTA2 expression. ERBB2, the predominant driver oncogene, was amplified in both sites, more pronounced in the lung, and harbored an L869R mutation in the lymph node. Functional studies showed increased proliferation, migration, metastasis, and resistance to ERBB2-directed therapy because of L869R mutation and increased migration because of ACTA2 overexpression. Within the lung, a nonfunctional CDK12, due to a novel G879V mutation, correlated with down-regulation of DNA damage response genes, causing genomic instability, and sensitivity to chemotherapy. We propose a model whereby a subclone metastasized early from the primary site and evolved independently in lymph nodes.